Research on relaxation characteristics of columnar jointed basalts of deep foundation in hydropower station - Gu, Jinjian; Wang, Jianxin; He, Mingjie; Yang, Shu; Li, Shuaikang (Frontiers in Physics, 2025)
The columnar basalt is a widely distributed in Southwestern China with different types. The first type of columnar jointed basalt is distributed below the elevation of 665 m on the left bank and 590 m on the right bank of the arch dam foundation. Micro-fissures are prevalent within the columns, with gently dipping structural surfaces and an intermittent mosaic structure despite poor overall integrity. The structure is easy to relax after unloading, and the acoustic wave of rock mass is obviously reduced. The control of relaxation deformation of columnar joint basalt is a key problem of hydropower exploration. Based on the structural of columnar jointed basalt, this paper analyzed the relaxation characteristics of columnar jointed basalt.